Minimum wage estimates and adjustments in Australia since 1983 - Cowie, Andrew; Jefferson, Therese (Centre for Research in Applied Economics, Curtin Business School, 2010)
This document provides estimates of national minimum wage rates for Australia since 1983. Providing estimates is not always a straight forward matter. We have provided a brief account of each wage decision providing: an estimated weekly minimum wage; an estimated hourly minimum wage based on the relevant standard working week; the relevant dollar increase; and the relevant percentage increase. We have also provided a summary of relevant events and submission from each decision in an endeavour to provide some of the social and political context for each decision.